Analisis Pengaruh Citra Merek, Suasana Toko, dan Kualitas Produk terhadap Keputusan Pembelian pada Bebek Goreng Pak Ndut Kartasura - Mufti Hidayatullah; Budi Sukardi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the impact of brand image on purchasing decisions, assess how the store atmosphere affects buying behavior, and evaluate the influence of product quality on purchase choices. The research employs a quantitative approach, targeting consumers who have made purchases at the Bebek Goreng Pak Ndut Kartasura outlet. Sampling was conducted using a non-probability purposive sampling technique. Data were gathered through questionnaires distributed to 160 respondents. The data analysis performed using IBM SPSS 25 software, the study variables including Brand Image, Store Atmosphere, Product Quality, and Purchasing Decisions. Findings reveal that brand image is affecting purchasing decisions. Similarly, the store atmosphere also has a significant positive impact. Product quality was found to positively and significantly influence consumers' purchase decisions as well. From these results, it can be concluded that improving management of brand image, product quality, and store atmosphere will likely enhance purchasing decisions on Bebek Goreng Pak Ndut Kartasura.